2013
DOI: 10.1017/jfm.2012.555
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity coefficients at excitation of cross-flow waves by free-stream vortices in the presence of surface roughness

Abstract: The present experimental study is devoted to examination of the vortex receptivity mechanism associated with excitation of unsteady cross-flow (CF) waves due to scattering of unsteady free-stream vortices on localized steady surface non-uniformities (roughness). The measurements are carried out in a low-turbulence wind tunnel by means of a hot-wire anemometer in a boundary layer developing over a 25 • swept-wing model. The harmonic-in-time free-stream vortices were excited by a thin vibrating wire located upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
61
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(84 citation statements)
references
References 52 publications
18
61
3
2
Order By: Relevance
“…Similarly, some experimental studies indicate an initial linear growth rate of the flow perturbation, for example Borodoulin et al [12], whilst others have observed a quadratic relationship in the 'linear' region (Kurian et al [13]). Note that a key difference between these experiments is that one used a swept--wing while the other used a swept flat plate.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, some experimental studies indicate an initial linear growth rate of the flow perturbation, for example Borodoulin et al [12], whilst others have observed a quadratic relationship in the 'linear' region (Kurian et al [13]). Note that a key difference between these experiments is that one used a swept--wing while the other used a swept flat plate.…”
Section: Introductionmentioning
confidence: 89%
“…As indicated by Borodulin et al (2013), almost all investigations related to unsteady vortex receptivity of boundary layers performed after the early experiments were theoretical ones until the end of the 1990s. For distributed roughness receptivity, considering a weak waviness, Zavol'skii, Reutov & Rybushkina (1983) theoretically investigated the problem of resonant scattering of a periodical vortex street on a wall, based on the framework of a locally parallel theory.…”
Section: Motivation Behind the Study Of Steps In Boundary Layersmentioning
confidence: 99%
“…Based on asymptotic theory, Goldstein (1983Goldstein ( , 1985, Ruban (1985) and Wu (2001a) carried out the studies for acoustic receptivity and Kerschen (1990), Goldstein & Leib (1993), Choudhari (1994) and Wu (2001a,b) for localised and distributed boundary layer receptivity. A detailed review work was done in the introduction of Borodulin et al (2013).…”
Section: Motivation Behind the Study Of Steps In Boundary Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Boundary layer receptivity problems have also been extensively analysed experimentally (see for example Kachanov et al 1979;Saric & White 1998;Dietz 1999;Borodulin et al 2013) and numerically (see for example Fucciarelli et al 2000;Wanderley & Corke 2001;Jones et al 2010;Tempelmann et al 2012). The main challenge of the experimental investigations is the measurement of the receptivity coefficients, since the initial amplitudes of the boundary layer instabilities may be orders of magnitude smaller than the amplitude of the surrounding disturbance environment.…”
Section: Introductionmentioning
confidence: 99%